2017
DOI: 10.1002/stem.2628
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Robo1 Regulates the Migration of Human Subventricular Zone Neural Progenitor Cells During Development

Abstract: SUMMARY Human neural progenitor cell (NPC) migration within the subventricular zone (SVZ) of the lateral ganglionic eminence is an active process throughout early brain development. The migration of human NPCs from the SVZ to the olfactory bulb during fetal stages resembles what occurs in adult rodents. As the human brain develops during infancy, this migratory stream is drastically reduced in cell number and becomes barely evident in adults. The mechanisms regulating human NPC migration are unknown. The Slit-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
(37 reference statements)
1
7
0
Order By: Relevance
“…The current study also identified that the expression of miR-218 was able to inhibit the high glucose-induced HUVEc proliferation, migration and angiogenesis by targeting ROBO1 and HO-1. A previous study verified that the high expression levels of ROBO1 and HO-1 were able to significantly increase cell migration, proliferation and angiogenesis (17,18,39). Herein, it was also observed that the expression of VEGF was increased in high glucose conditions.…”
Section: Discussionsupporting
confidence: 61%
“…The current study also identified that the expression of miR-218 was able to inhibit the high glucose-induced HUVEc proliferation, migration and angiogenesis by targeting ROBO1 and HO-1. A previous study verified that the high expression levels of ROBO1 and HO-1 were able to significantly increase cell migration, proliferation and angiogenesis (17,18,39). Herein, it was also observed that the expression of VEGF was increased in high glucose conditions.…”
Section: Discussionsupporting
confidence: 61%
“…Primary fetal neural progenitor cells (NPCs) were utilized as a healthy brain tissue control in order to assess the cell type specificity of siRNA delivery via R646. [16,17,49] NPCs are obtained as described previously following procedures approved by the Johns Hopkins University Institutional Review Board. [50] NPCs 34, 54, and 61, with each number indicating different tissue samples, were used to provide three separate cell source samples.…”
Section: Cell Culturementioning
confidence: 99%
“…[15] siRNA is promising as a therapeutic to treat brain cancer for several reasons: i) it can hit targets that are seen as "undruggable" by conventional medicinal approaches; ii) it has the potential of overcoming drug resistances by affecting multiple disease-causing biochemical pathways in parallel; iii) it does not necessarily require reformulation of a drug delivery particle when the type of siRNA cargo changes; and, unlike DNA, iv) it does not risk introducing inheritable genetic changes. Protein targets of particular interest to us include Roundabout homolog 1 (Robol), a protein identified as key to normal and cancer cell migration; [16][17][18] yes-associated protein 1 (YAP1), which promotes growth of GBM cells; [19,20] sodium-potassium-chloride cotransporter (NKCC1), an ion transporter that affects cancer cell migration; [21,22] survivin, an anti-apoptotic gene whose expression in GBM correlates with proliferation [23] and with poor prognosis; [24] and endothelial growth factor receptor (EGFR), an oncogene whose aberrant expression is among the most common mutations in GBM. [25][26][27] Other reports of knockdown of Robo1, [18] YAP1, [28] NKCC1, [21,29] survivin, [30] or EGFR [31] often focus on knockdown of a single gene to isolate cellular mechanisms of GBM survival, growth, and invasion.…”
Section: Introductionmentioning
confidence: 99%
“…The SVZ is the largest neurogenic niche in adults and is highly regulated by the flow of cerebrospinal fluid (CSF). The CSF milieu has the properties to sustain the neurogenic niche environment, regulating neural stem cells proliferation, differentiation, and migration (13,(16)(17)(18). Given the neurogenic potential that CSF holds on NSCs and the similarities between NSCs and BTICs, we explored the possibility that CSF might similarly affect GBM proliferation, differentiation, and migration.…”
Section: Introductionmentioning
confidence: 99%